Deciphering the Degradation Mechanisms and Realize High‐Voltage Stability of A3V2(PO4)3 (A = Li+, Na+) in Aqueous Dual‐Ion Batteries - Dong, Chongrui; Chen, Yuanjing; Ding, Yan; Pu, Xiangjun; Cao, Yuliang; Ma, Zhongyun; Chen, Zhongxue (Small (Weinheim an der Bergstrasse, Germany), 2024)
Polyanionic A3V2(PO4)3 (A = Li+, Na+) with open channels have been extensively utilized as cathode materials for aqueous zinc‐metal batteries (AZMBs), whereas suffering from severe capacity fading and rapid operation voltage decay during cycling. when used as In this work, it is disclosed that the rapid degradation is induced by an irreversible phase change from electrochemical active Li3V2(PO4)3 to nonactive monoclinic LiZnPO4, as well as active Na3V2(PO4)3 to nonactive rhombic Zn3(PO4)2(H2O)4. Subsequently, a rational dual‐cation (Al‐Fe) doping strategy is proposed to suppress these detrimental transformations. Such dual‐cation doping entails stronger P–O and V–O bonds, thus stabilizing the initial polyanionic structures. Consequently, the optimized member of Li3V1.775Al0.075Fe0.225(PO4)3 (LVAFP) exhibits desirable cycling stability (1000 cycles, 68.5% capacity retention) and notable rate capability (92.1% of the initial capacity at 10 C). Moreover, the dual‐cation doping methodology is successfully extended to improve the stability of Na3V2(PO4)3 cathode in aqueous dual‐ion batteries, signifying the versatility and feasibility of this strategy. The comprehensive identification of local structural evolution in these polyanions will broaden the scope of designing high‐performance alkali‐vanadyl‐phosphates for multivalent aqueous batteries. The Li3V1.775Al0.075Fe0.15(PO4)3 cathode exhibits improved cycling stability and capacity retention in aqueous dual‐ion (Li, Zn) batteries, and the dual metal doping (Al, Fe) strategy is successfully extended to improving the stability of Na3V2(PO4)3 cathode, thereby opening a new avenue to promote the development of high‐performance alkali vanadyl phosphates for aqueous batteries.